Pengaruh CSR dan Profitabilitas Terhadap Nilai Perusahaan - Lubis, Nurul Azhrah; Nurwani, Nurwani (Universitas Labuhanbatu, 2024)
This study aims to determine the effect of Corporate Social Responsibility and profitability on the value of the company in mining companies listed diBEI year 2016-2020. The type of data used in this study is quantitative data. The method used in this study is purposive sampling method with a population of 49 companies and a sample of 6 companies. The technique of data collection in this study is using the documentation method and analyzed by multiple linear regression analysis using SPSS 22 application. The results showed that (1) profitability and CSR disclosure had a positive and significant effect on the value of the Company, (2) profitability had a positive and significant effect on the value of the company, and (3) CSR disclosure and profitability had a positive and significant effect on the value of the company simultaneously.